MONITORING SIDE EFFECTS OF ANTIRETROVIRAL THERAPY IN PATIENTS WITH HUMAN IMMUNODEFICIENCY VIRUS/ACQUIRED IMMUNODEFICIENCY SYNDROME - Sari, Santi Purna; Isnaini, Siti Rizky; Puspitasari, Atika Wahyu (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to monitor the side effects of patients who received antiretroviral medications in a subdistrict of West Jakarta in 2017. Methods: Descriptive research was performed using data collected prospectively from patients who met our inclusion criteria (total sampling). Primary data were obtained from interviews, and secondary data were obtained from medical and prescription records. The Naranjo algorithm was used to classify side effects. Results: The side effects experienced by patients in this study fell into probable (45.45%) and possible (36.36%) categories. However, age (p=0.379), gender (p=1), and length of treatment (p=0.07) did not significantly affect the occurrence of side effects. Conclusion: Monitoring the side effects of antiretroviral medicine is necessary to prevent serious and rare side effects. The occurrence of side effects, whether they have an established causal relationship or not, could be prevented by appropriate monitoring.